Efektivitas Latihan Distance To Distance dan Interval With Mini Hurdle dalam Meningkatkan Kecepatan dan Daya Tahan Atlet Jarak Menengah - Karin Setya Arzety; Oce Wiriawan; Fifit Yeti Wulandari; Bhekti Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effectiveness of two training models, distance to distance and interval with mini hurdle, in improving the speed and endurance of middle-distance runners. The main problem addressed is the need for a training approach capable of simultaneously optimizing speed and endurance performance through the integration of physiological and biomechanical components. This research employed a quasi-experimental method with a pretest–posttest two group design. The subjects were 15 male middle-distance athletes (800–1500 m) randomly divided into two groups, each undergoing an eight-week training program with a frequency of three sessions per week. Measurements were conducted using a 30-meter sprint test (speed) and a 1600-meter run test (endurance). Statistical analysis showed that both training models significantly improved speed and endurance variables (p < 0.05). The interval with mini hurdle group demonstrated a higher improvement in speed (10.5%) with a large effect size (d = 1.45), while the distance to distance group achieved a 7–8.5% improvement in endurance. A significant difference between groups was found in the speed variable (p = 0.034; d = 0.91). The study concludes that both training models effectively enhance athlete performance, with interval with mini hurdle being superior in developing speed through neuromuscular stimulation, whereas distance to distance focuses more on improving aerobic endurance. Conclusion, these findings provide a scientific basis for coaches to design evidence-based, efficient, and measurable training programs. Keywords: interval training, speed, endurance, middle-distance running.